"Social Movement Theory" as a Baseline Legitimizing Narrative: Corporate Exploitation, Anti-Hegemonic Opposition and the Contested Academy. Issue 1 (March 2017) - Jackson, Nicholas A.
Scholars and administrators created "Social Movement Theory" (SMT) and associated institutions in order to establish a field of "contested politics" buttressed by "scholarly synthesis." In this article, I place SMT as an object of study itself within the contested space of the corporate academy. SMT is a baseline legitimizing narrative that the domesticated academy produces and that corporate entities then use as preemptive inoculation against anti-hegemonic opposition by geographically separating governmentalities of often brutal and arbitrary material exploitation from depoliticized, dehistoricized and scientistic spectacles of consumerist legitimization. I summarize key ways that administrators govern the corporate academy and remove historical and social specificity, followed by analysis of exemplary cases demonstrating how SMT is placed within "peer-reviewed" scholarship. In contrast to SMT's over-riding goal of "synthesis, " I argue that effective social movement scholarship is contingent, situated and explicitly engaged with power (willing to "reveal a stand"), including difficult questions about who exercises power, how, and especially under what guises of corporate authority. Done well, such intellectual-activism must be conducted independent of current corporate academic strictures, and indeed will likely involve direct anti-hegemonic challenges to the corporate academy. Intellectual-activists that choose to do so can face significant negative impacts ranging from "double-shift" marginalization through loss of academic privileges, total career destruction, banishment from the academic canon and even physical endangerment. Therefore, effective transformation of social movement scholarship requires transformation of the contested academy, both projects very difficult for embedded academics absent external pressure from intellectual-activists.